Analisis Pengaruh Penjabat Bupati dalam Kontestasi Pilkada - Boby, Feramita Hasani; Gazalin, Junaid; Restiawati, Restiawati; Zulhidayat, M Reyza; Ananto, Muh Aldi Musbaq (CV. ULIL ALBAB CORP, 2025)
Acting regents play an important role in the political process of Regional Head Elections (Pilkada) in Indonesia, especially in the transition period between the resignation of the previous official and the implementation of the next election. This study aims to analyze the influence of acting regents on the dynamics of political contestation in Pilkada, using a qualitative approach through surveys and in-depth interviews. The results show that the acting regent has a significant influence on voters, both through policies taken during the term of office and direct influence on regional head candidates. Despite the potential for abuse of power, the majority of respondents considered that the role of the acting regent was more about regulating regional administration than directly intervening in practical politics. This study suggests the need for stricter regulations regarding the involvement of acting regents in the political process in order to maintain the integrity of Pilkada.